IDENTIFICATION OF RACIAL AND ETHNIC DISCRIMINATION ACCORDING TO LAW NUMBER 40 OF 2008 AND DISCRIMINATION WOMEN ACCORDING TO LAW NO. 7 OF 1984 IN CIVIL CODE - Hasyim, Dardiri (DERECHTSSTAAT, 2018)
This research attempts to find forms of discrimination in the Act No. 40 of 2008, Act No. 13 of 2003, as well as Act No. 7 of 1984, and compare with Civil Code. Research using the method of librarianship. The results showed there are 19 articles in the Civil Code which is discriminatory. Â In the meantime there are 6 forms of discrimination in the Act No. 40 of 2008; and 17 form in Act No. 7 of 1984.